Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Keuangan Pada PT. Astra Internasional Daihatsu, Tbk - Leidy Y. Kawengian; Henny S. Tarore; Dantje Keles (JURNAL ADMINISTRASI BISNIS, 2018)
This research is explanatory, that is research whose purpose is to examine various relationship of hypothesized variables. The variables used in this study are capital structure or debt equity ratio,Current ratio (CR), Net Provit Margin (NPM), as well as Return On Assets (ROA). As one of the reference in measuring the amount of profit becomes so important to know. whether the company has run its business efficiently, because the new efficiency can be known by comparing the profit earned with the asset or capital that produces the profit or calculates profitability.This study aims to analyzeÂ  the simultaneous and partialinfluence of Current Ratio (CR) factors, capital structure or debt equity ratio (DER) and Net Provit Margin (NPM) on return on Assets (ROA) at PT. Astra Internasional Daihatsu Tbk.This research is explanatory, that is research whose purpose is to examine various relationship of hypothesized variables.The result of this study indicate that the liquidity ratio and solvency ratio to measure the companyâ€™s ability to meet its short-term obligations through the curren ratio indicator is in the â€œ good enoughâ€ performance category when compared to the industry standard average, The result of multiple linear regression analysis show that all three factors (CR,DER and NPM) simultaneously have no significant but positive effect on financial performance (ROA) of PT Astra Internasional Daihatsu Tbk, while partially the dominant factor influencing financial performance (ROA) of PT Astra Internasional Daihatsu Tbk is a Debt Equity Ratio (DER). It is recommended that PT Astra Internasional Daihatsu Tbk should focus its attention on the companyâ€™s liquidity (curren ratio), must focus more on debt equity ratio (DER) because its influence is quite dominant on financial performance(ROA), and must focus more on net profit margins due to its influence even though it is not real but positive toward financial performance (ROA).Keyword :Â  Return On Asset (ROA), Capital Structure or Debt Equity Ratio (DER),Current Ratio(CR), and Net Provit Margin (NPM), and Financial Performance